The effect of Financial Literacy, Access to Finance, and Financial Risk Attitude on the Culinary Business Performance of SMEs in Yogjakarta - Gusaptono, Raden Hendri; Kristanto HC, R. Heru; Yulita, Lita (Technium Social Sciences Journal, 2023)
Individuals, households, and business entities that have met the criteria as businesses have SMEs as productive businesses. Micro, small, and medium enterprises (SMEs) significantly contribute to a region’s economic development. Financial literacy, access to finance, and financial risk attitude are important in improving business performance. This study aimed to examine the effect of financial literacy on access to finance, financial risk attitude, and culinary business performance. Test mediating roles access of finance and financial risk attitude on the impact of financial literacy on the performance of the MSME culinary business in Yogyakarta. Statistical analysis model using mediation regression. The research sample is the Actor Culinary business SMEs in Yogyakarta. Sampling technique with purposive sampling. Respondents were 135 SME Culinary Entrepreneurs. Mediation regression analysis tool using PLS. The research results show that: 1) Financial literacy positively affects culinary business performance. 2) Financial literacy has a positive effect on access to finance. 3) Access to finance mediates the effect of financial literacy on culinary business performance. 4) Financial literacy has a positive effect on financial risk attitudes. 5) Financial risk attitudes mediate the effect of financial literacy on culinary business performance. The research results recommend the importance of increasing financial literacy and ease of access to finance. Analyzing risk is needed for SME culinary business actors to improve business performance and sustainability.